(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
Chile, despite having a migration history, has not generated educational programs supported by government policies that encourage the acquisition of the linguistic variety of the host society, by non-Spanish-speaking immigration community, integrating the cultural referents of both collectives. It is suggested an option to this historical oblivion and we consider the following: What elements should be integrated into a program for acquiring the linguistic variety of the host society focused to Haitian immigrants fostering the cultural recognition? It is presented the design and implementation of a program that adopts the Linguistic Interdependence Hypothesis in a dynamic classroom working in a collaborative and situated way. As a conclusion, it is possible to educate in a second language from a program that incorporates elements that promote the interrelation of all participants in equality of knowledge, as well as the use of participants’ linguistic codes as a manifestation of respect and interest for what each participant can contribute from his/her L1, revealing their culture of origin.